Supra-physiological dose of testosterone induces pathological cardiac hypertrophy. Issue 1 (April 2016) - Pirompol, Prapawadee; Teekabut, Vassana; Weerachatyanukul, Wattana; Bupha-Intr, Tepmanas; Wattanapermpool, Jonggonnee
Abstract : Testosterone and androgenic anabolic steroids have been misused for enhancement of physical performance despite many reports on cardiac sudden death. Although physiological level of testosterone provided many regulatory benefits to human health, including the cardiovascular function, supra-physiological levels of the hormone induce hypertrophy of the heart with unclear contractile activation. In this study, dose- and time-dependent effects of high-testosterone treatment on cardiac structure and function were evaluated. Adult male rats were divided into four groups of testosterone treatment for 0, 5, 10, and 20 mg/kg BW for 4, 8, or 12 weeks. Increases in both percentage heart:body weight ratio and cardiomyocyte cross-sectional area in representing hypertrophy of the heart were significantly shown in all testosterone-treated groups to the same degree. In 4-week-treated rats, physiological cardiac hypertrophy was apparent with an upregulation of α-MHC without any change in myofilament contractile activation. In contrast, pathological cardiac hypertrophy was observed in 8- and 12-week testosterone-treated groups, as indicated by suppression of myofilament activation and myocardial collagen deposition without transition of MHC isoforms. Only in 12-week testosterone-treated group, eccentric cardiac hypertrophy was demonstrated with unaltered myocardial stiffness, but significant reductions in the phosphorylation signals of ERK1/2 and mTOR. Results of our study suggest that the outcome of testosterone-induced cardiac hypertrophy is not dose dependent but is rather relied on the factor of exposure to duration in inducing maladaptive responses of the heart.